A história nas telas: arte e memória na série "O Cassino da Maroca" de Ruth Schneider - Carmo, Aline do (2015)
This study conducts a hybrid research, with historical aspect elements, biographical, artistic and social, on the theme represented in four works in the series Casino Maroca, artistic production of the painter Ruth Schneider. For it was studied the characters and scenarios represented on screen, from the private archives of the artist, looking to make a dialogue with the stories of this place and its characters as also with their social and cultural aspects of this notorious cabaret in Passo Fundo the decades 40 and 50. However, when transcribing the Ruth Schneider of manuscripts for this job, it was found that the production of the artist, there was much more than just the representation of their childhood memories, there was also a morass of information personal (marriage and maternity), historical (cabaret and society) and social (prostitution in the society of the time). Aspects that generate meaning in the stories that break these frames. Ruth Schneider, painter, engraver, designer, self-taught, was an artist who always chose to draw plural paths and experience different languages and supports. By its libertarian stance, the research found in the series of paintings Casino Maroca, the thread running through the multiplicity of characters and their stories. Recognizing the painter as affiliated with the romantic conception, that the artist does not separate his art from his own life, the work draws on theoretical approaches geared to relations between the biography and the artistic work, realizing the influence of apparently extrinsic evidence - particularly the history and society - as constituents and sense of artistic product generators. In the analysis of the works of Ruth Schneider, are characteristics of a poetic break that organically link to their childhood experiences in Passo Fundo. Similarly the force with which expresses these stories leave explicit social critic aspect of his art.